Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content: 1. A sociological analysis of perceptions of work motivation among young people and its relationship to unemployment: A field study in Ngoussa – Algeria Mr. Masoudi Abdel Basset, Professor Dr. Bin Issa Muhammad Al Mahdi 2. The Effect of Climate on Residential Electrical Energy Consumption in Jeddah City Ms. Khadija Muhammad Samili, Dr. Faida Kamel Boqri 3. The Stress System of English Loanwords in Qassimi Arabic: An Optimality Theoretic Analysis Dr. Nuha Naser Alluhaidan 4. The Concept of ‘Supernaturalism’ in British and American Fiction: A Comparative Study Ms. Areej Mohammed Mubarak Ali